2022
DOI: 10.1242/dmm.049481
|View full text |Cite
|
Sign up to set email alerts
|

Collagen VI deficiency causes behavioral abnormalities and cortical dopaminergic dysfunction

Abstract: Mutations of genes coding for Collagen VI (COL6) cause muscle diseases, including Ullrich congenital muscular dystrophy (UCMD) and Bethlem myopathy (BM). Although more recently COL6 genetic variants were linked to brain pathologies, the impact of COL6 deficiency in brain function is still largely unknown. Here, a thorough behavioral characterization of COL6 null (Col6a1−/–) mice unexpectedly revealed that COL6 deficiency leads to a significant impairment in sensorimotor gating and memory/attention functions. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…Besides the already described role of COL6 in the satellite cell niche of skeletal muscles, where it sustains self-renewal and tissue regeneration [ 24 ], the proper expression and ECM deposition of COL6 in the nervous system has been recently linked to the ability of several brain compartments, including blood vessels and meninges, but also neurons and glial cells, to correctly develop and differentiate into mature functional entities [ 63 , 64 ]. Our data demonstrate that COL6 plays a pivotal role also in the brain tumor context, supporting the generation of a favorable microenvironment for GSC maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the already described role of COL6 in the satellite cell niche of skeletal muscles, where it sustains self-renewal and tissue regeneration [ 24 ], the proper expression and ECM deposition of COL6 in the nervous system has been recently linked to the ability of several brain compartments, including blood vessels and meninges, but also neurons and glial cells, to correctly develop and differentiate into mature functional entities [ 63 , 64 ]. Our data demonstrate that COL6 plays a pivotal role also in the brain tumor context, supporting the generation of a favorable microenvironment for GSC maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study has linked COL6A2 gene mutations to progressive myoclonus epilepsy 67 , while polymorphisms of several COL6A genes are identified as rare risk factors for schizophrenia and bipolar disorders 68 . A recent behavioral study showed that Col6a1 deficiency results in social memory and object recognition impairment, which is associated with decreased brain dopamine and 5-HT levels 69 . It is thus conceivable that changes in collagen gene expression may contribute to abnormal spine/synapse maturation, circuitry wiring, and cognitive functions in AS.…”
Section: Discussionmentioning
confidence: 99%
“… ABSTRACT First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping researchers promote themselves alongside their papers. Ilaria Gregorio is first author on ‘ Collagen VI deficiency causes behavioral abnormalities and cortical dopaminergic dysfunction ’, published in DMM. Ilaria conducted the research described in this article while she was a PhD student in Paolo Bonaldo and Matilde Cescon's lab at the University of Padova, Italy.…”
mentioning
confidence: 99%